2019
DOI: 10.1007/s42452-019-1392-5
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing and predicting the relation between air–fuel ratio (AFR), lambda (λ) and the exhaust emissions percentages and values of gasoline-fueled vehicles using versatile and portable emissions measurement system tool

Abstract: Reducing vehicles exhaust emissions pollution associated with gasoline combustion become growing interest locally and global-wide. To satisfy the exhaust gas emissions rules and regulations it is very significant and critical for gasoline internal combustion engines to have an accurate control of air-fuel ratio (AFR). Therefore, studying the relationship between the AFR, lambda (λ) and the exhaust emissions of gasoline-fueled vehicles is very important and necessary. A sensitive and detailed analysis conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 3 publications
1
10
0
1
Order By: Relevance
“…Comparing stoichiometric (AFR = 1) and lean (AFR = 1.7) engine operation with the uncoated adapter, it can be observed that the unburned fuel hydrocarbons (C 2 H 5 OH, C 5 H 12 , C 4 H 10 ) significantly increase at lean engine operation, while the intermediate hydrocarbon species (C 2 H 2 , C 6 H 6 ) and carbon monoxide (CO) decrease with lean engine operation. This can also be observed for the raw emissions of an SI engine. By applying an LSCO layer of 60 μm to the valve adapter, a significant reduction of the hydrocarbons and carbon monoxide can be observed for lean and stoichiometric operation (see Figure ).…”
Section: Resultsmentioning
confidence: 63%
“…Comparing stoichiometric (AFR = 1) and lean (AFR = 1.7) engine operation with the uncoated adapter, it can be observed that the unburned fuel hydrocarbons (C 2 H 5 OH, C 5 H 12 , C 4 H 10 ) significantly increase at lean engine operation, while the intermediate hydrocarbon species (C 2 H 2 , C 6 H 6 ) and carbon monoxide (CO) decrease with lean engine operation. This can also be observed for the raw emissions of an SI engine. By applying an LSCO layer of 60 μm to the valve adapter, a significant reduction of the hydrocarbons and carbon monoxide can be observed for lean and stoichiometric operation (see Figure ).…”
Section: Resultsmentioning
confidence: 63%
“…The stoichiometric air to fuel ratio, also defined as λ = 1, where λ is defined as the air/fuel equivalence ratio, is when all three pollutants can be converted [14]. A mathematical relationship can be used to define the air/fuel equivalence ratio [60]. λ = AFR AFR stoichio (7) where AFR is the actual air/fuel ratio, and AFR Stoichio is the stoichiometric air/fuel ratio.…”
Section: Air/fuel Equivalence Ratiomentioning
confidence: 99%
“…λ = AFR AFR stoichio (7) where AFR is the actual air/fuel ratio, and AFR Stoichio is the stoichiometric air/fuel ratio. Rich air-fuel mixtures have λ < 1, and lean air/fuel mixtures have λ > 1 [60].…”
Section: Air/fuel Equivalence Ratiomentioning
confidence: 99%
“…On the contrary, an EA ratio above 0.79 lowers NOx emissions and increases CO and SO 2 . Al-Arkawazi [6] studied the effect of the air-fuel ratio and lambda (λ) on the exhaust emissions from internal combustion engines and provided a curve of direct relationship between them.…”
Section: Introductionmentioning
confidence: 99%